Case report: Incomplete bypass ileocolostomy without partial typhlectomy in five horses with acute, non-reducible cecocolic intussusceptions and review of literature - Troillet, Antonia; Scharner, Doreen (Frontiers in Veterinary Science, 2024)
Cecocolic intussusceptions are a rare condition of acute colic in horses requiring immediate surgical intervention due to persistent uncontrollable pain and ongoing ischemic cecal necrosis. Particularly in cases where reduction of the intussusception is surgically not feasible surgical interventions such as partial typhlectomy through colotomy (partial cecal amputation) combined with or without cecal bypass techniques are described. Alternatively, surgical interventions can also be performed without partial typhlectomy via incomplete bypass ileocolostomy. Information regarding applicable techniques and outcomes base on sparse literature of single case reports or small case series. Therefore, this case series aims to add more cases treated with incomplete bypass ileocolostomy without typhlectomy to existing literature and to compare the outcome by reviewing medical records from January 2009 to March 2024 in context to literature. Five horses were surgically treated and were followed-up between 1 and 9 years. Minor short-term complications were recorded during hospitalization such as transient mild colic and febrile episodes. Long-term outcome revealed that horses received or exceed their previous level of use. By adding the hereby presented cases to published data horses treated with ileocolostomy without partial typhlectomy had a long-term survival rate of 100%. However, numbers of published cases are still low with 49 horses being included in the literature review whereof 42 recovered from surgery. The overall long-term survival rate was 53%. The added value of this study is based on the comprehensive documentation of a cohort of five horses successfully treated with an incomplete bypass procedure, demonstrating favorable long-term outcomes. Furthermore, the study advances the surgical technique by implementing the closure of mesenteric gap. The evidence for the application of the surgical technique has been strengthened.